Uso da acrilamida e diferentes protocolos de aplicação de um sistema adesivo universal na resistência de união à dentina - Carvalho, Marcos Paulo Marchiori (2017)
This study aims to test different adhesive protocols, as well as influence of chemical changes of Single Bond Universal to verify improvement in bond strength and stability of the hybrid layer. One hundred and forty-four teeth was obtained through the Bank of Human permanent teeth of UFSM and randomly assigned to each group, divided by the type of application protocol (control, Chlorhexidine, Warm Air, Double adhesive application, Photoactivation for 40 seconds and "All in One"), the type of adhesive (Single Bond Universal and Single Bond Universal modified) and storage time (24 hours and 06 months). To test the effects of the chemical change versus protocol was used a single multi-mode ethanol-based adhesive (Single Bond Universal) to isolate the chemical composition factor. Changes in chemical composition were held by incorporating the adhesive of a acrylamide of pharmaceutical use. The addition of the polymer will occur in a concentration of 1ml/0,05ml the adhesive to generate a different versions to be tested. To analyze the differences between the two adhesives, ultimate bond strength analyzes was made to compare properties of the universal single bond with the universal single bond modified. To verify differences in the hybrid layer and the bond strength between the adhesive and the different application protocols, microtensile tests was done. The conceptual hypothesis of this study is that altered viscosity and different application protocols will improve adhesive properties and long-term bond strength. The null hypothesis is that changes in the protocol and viscosity of the adhesive do not result in significant improvements in outcomes studied. The results observed in the two articles showed an increase in dentin bond strength when an adhesive with addition of acrylamide was used, as well as an increase in its intrinsic resistance verified by ultimate tests in both articles. Among the protocols, the group "all-in-One" obtained the best results but without statistical difference compared to Chlorhexidine, Warm air and Double Application. The Control group presented the worst result however was not statistically worse than the 40s Group. The addition of acrylamide in a universal ethanol based adhesive increased its intrinsic resistance as well as the dentin bond strength. Some changes in the adhesive´s protocol of a universal adhesive also increased the dentin bond strength.